Alternate Access for TAVI: Stay Clear of the Chest - Overtchouk, Pavel (Interv Cardiol, 2018)
Transcatheter aortic valve implantation (TAVI) is currently performed through an alternative access in 15% of patients. The transapical access is progressively being abandoned as a result of its invasiveness and poor outcomes. Existing data does not allow TAVI operators to favour one access over another — between transcarotid, trans-subclavian and transaortic — because all have specific strengths and weaknesses. The percutaneous trans-subclavian access might become the main surgery-free alternative access, although further research is needed regarding its safety. Moreover, the difficult learning curve might compromise its adoption. The transcaval access is at an experimental stage and requires the development of dedicated cavo-aortic crossing techniques and closure devices.